Clinico‐genetic study of two Japanese pedigrees with hereditary spastic paraparesis and Alzheimer's disease: Genetics/molecular genetics. (7th December 2020) - Rumore, Roberto; Montecchiani, Celeste; Gaudiello, Fabrizio; Miele, Marialuisa; Kawarai, Toshitaka; Orlacchio, Antonio
Abstract: Background: Mutations in the SPG4/ SPAST gene are the major cause of hereditary spastic paraplegias (HSPs), a group of genetic disorders leading to progressive spasticity and weakness of the lower limbs. Alzheimer's disease (AD) is a degenerative disorder of the central nervous system. Early‐onset familial AD (EOFAD) accounts for 3‐5% of all AD cases and denotes families in which onset is reliably before age 60 to 65 years and often before age 55 years. The present study reports a second Japanese pedigree in which a SPG4/ SPAST mutation co‐segregates with HSP and EOFAD. Method: Whole exome sequencing (WES), Sanger sequencing, Multiplex Ligation dependent Probe Amplification (MLPA) analysis, bioinformatics, neurological evaluation, diagnostic imaging, and pathological assessment. An SPG4/ SPAST Japanese family with similar genotype‐phenotype findings was already described by our research team. Haplotype analysis was conducted on the two pedigrees. Result: One Japanese man was diagnosed as certainly affected by slowly progressive autosomal dominant HSP, according to the Harding criteria. The age at onset of the first motor symptoms was 31 years. At 52 years, phenotype was complicated by cognitive impairment; a diagnosis of probable EOFAD following the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association (NINCDS‐ADRDA) criteria was formulated. The case was definite Alzheimer's disease (autopsy proven): the brain pathology revealed plaques with a congophilic core and neuritic pathology. Both the brother and the son of the proband revealed the same initial symptoms of dementia and HSP was diagnosed, respectively, at age 55 and 34 years. WES revealed in all the patients a heterozygous change in SPAG4/ SPAST . MLPA analysis excluded the presence of deletions/duplications in SPG4/ SPAST . Haplotype analysis disclosed a founder effect for the mutation in the two families sharing the same clinico‐genetic characteristics. Bioinformatic analyses and population study confirm a pathogenetic role of such mutation. Screening of PS1, PS2, and b APP genes did not reveal any coding mutation. No affected subject carried out APOE genotype ε4/ε3 or ε4/ε4. Conclusion: This work describes the second Japanese family with a SPAG4/ SPAST mutation and association of HSP and EOFAD. A possible founder effect was confirmed by haplotype analysis.